2020
DOI: 10.1101/2020.07.27.223438
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polycomb-mediated Genome Architecture Enables Long-range Spreading of H3K27 methylation

Abstract: SUMMARYPolycomb-group proteins play critical roles in gene silencing through the deposition of histone H3 lysine 27 trimethylation (H3K27me3) and chromatin compaction1-5. This process is essential for embryonic stem cell (ESCs) pluripotency, differentiation, and development. Polycomb repressive complex 2 (PRC2) can both read and write H3K27me3, enabling progressive spread of H3K27me3 on the linear genome6. Long-range Polycomb-associated DNA contacts have also been described, but their regulation and role in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 70 publications
(74 reference statements)
3
19
0
Order By: Relevance
“…In summary, we applied HiCAR to H1 hESCs, and took advantage of the rich epigenome datasets generated from the same cell type by ENCODE, Epigenome Roadmap, and 4DN consortiums for integrative analysis. Consistent with recent studies showing that H3K27me3 and PRC2 are associated with extensive chromatin interactions anchored on the genes important for development 33,36 . In our study, we also found that the poised/bivalent promoter/enhancer marked by H3K27me3 and/or SUZ12 are associated with significant chromatin interactions near genes important for development.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In summary, we applied HiCAR to H1 hESCs, and took advantage of the rich epigenome datasets generated from the same cell type by ENCODE, Epigenome Roadmap, and 4DN consortiums for integrative analysis. Consistent with recent studies showing that H3K27me3 and PRC2 are associated with extensive chromatin interactions anchored on the genes important for development 33,36 . In our study, we also found that the poised/bivalent promoter/enhancer marked by H3K27me3 and/or SUZ12 are associated with significant chromatin interactions near genes important for development.…”
Section: Discussionsupporting
confidence: 92%
“…GO analysis showed that H3K27ac anchors are enriched for GO terms such as gene expression, metabolic, chromatin organization, and stem celll proliferation/maintenance, while the H3K27me3 anchor sequences are enriched for GO terms important for tissue and organ development. Our finding that the poised/H3K27me3 mark cREs are associated with extensive, long-range chromatin interaction is consistent with a recent study showing that H3K27me3-associated DNA interactions tend to span long-range and even across multiple topologically associated domains in mouse ESCs and human induced pluripotent stem cells 33 . However, these H3K27me3 anchored interactions were identified by H3K37me3 HiChIP analysis, thus, it remains challenging to compare these "poised" interactions to the chromatin interactions associated with different epigenetic modifications.…”
Section: Hicar Is a Robust And Sensitive Methods To Identify Cis-regulsupporting
confidence: 92%
“…Moreover, TFs have been reported to mediate long-range chromatin contacts through direct homodimerization (e.g. YY1) or protein-protein interactions with other bona fide architectural factors, such as cohesin or PRC2 components (120,(140)(141)(142)(143). Importantly, the expression and/or genomic distribution of many of these critical factors (TFs and histone modifications) change during B and T cell development and activation, therefore they might contribute to the observed 3D chromatin reorganization.…”
Section: Chapter Iv: Presumed Mechanisms and Players Of 3d Chromatin Reorganization During B/t Lymphopoiesismentioning
confidence: 99%
“…3,27,30 Recent studies have demonstrated that high levels of H3K27me3, often within CpG hypomethylated regions, can mediate long-range chromatin interactions spanning from DNA loops to self-associating domains. [31][32][33][34][35][36][37][38] These H3K27me3-mediated interactions have been implicated in the regulation of key developmental genes and are distinct from canonical structures regulated by CTCF and cohesin. [31][32][33][34][35][36][37][38] However, how Polycomb interactions and H3K27me3 impact compartmentalization, nuclear positioning, and heterochromatin organization remains to be fully resolved.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38] These H3K27me3-mediated interactions have been implicated in the regulation of key developmental genes and are distinct from canonical structures regulated by CTCF and cohesin. [31][32][33][34][35][36][37][38] However, how Polycomb interactions and H3K27me3 impact compartmentalization, nuclear positioning, and heterochromatin organization remains to be fully resolved. 6,7 Deconvoluting how these layers of genome organization control cell-type specific expression programs will further our understanding of Polycomb Group (PcG) proteins and the roles they play in development and disease.…”
Section: Introductionmentioning
confidence: 99%